Inovasi Produk Berbahan Ikan sebagai Makanan Berprotein pada Masa Pandemi - Nur Rasdianah; A Mu’thi Andy Suryadi (Jurnal Pengabdian Pada Masyarakat, 2021)
INNOVATIION OF FISH PRODUCTS AS PROTEIN FOOD IN THE PANDEMIC TIME. Efforts to increase immunity amid the Covid-19 pandemic can be made by eating nutritious foods. The nutritional aspect in the form of protein in fish can prevent infection from bacteria, fungi, and viruses. The implementation of community service in fish-based protein food innovation was carried out by providing training in making snacks in Solo Fish Sausage and Fish Nugget. Varied food processing will also improve the family economy. The service method is product training, packaging and labeling procedures, and product marketing methods. The training participants are residents of Malango village. Delivering material by lecturers and mentoring in manufacturing practices, product packaging by students. Then proceed with the second material about the concept of entrepreneurship and marketing procedures as a solution to increase family income during a pandemic. After attending the training and enjoying the products made, the participants were satisfied and hoped that similar exercise could be carried out again.